Transfer Features poems of Hafiz. - Akhmetbekova., A.; Ryszhanova., E. (Journal of Oriental Studies, 2016)
In the article translation is considered as an interpretation. The authors through comparisons translation Hafiz gazelles in the Kazakh language, note that transfers Shakarima Kudayberdiuly gravitated to the tradition of "Nazir"